Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68089
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Local Heat Transfer Enhancement in a Rectangular Dimpled Channel With a Large Aspect Ratio

Abstract: In this paper the convective heat transfer in a rectangular dimpled channel with an aspect ratio of six is studied. Applications could be for gas turbine vanes, vane shrouds, ring segments and hot components in the combustor. Basic heat transfer experiments have been performed using heater foils and a steady-state method with liquid crystals. The cooling effect is achieved by a dimple configuration combined with rib turbulators. The specific subject of this study is to focus on the heat transfer enhancement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Shen et al [ 15 ] experimentally and numerically studied the heat transfer and pressure drop characteristics in blade trailing edge trapezoidal and rectangular cooling passages with dimples under the effect of ejection slots. Lauffer et al [ 16 ] set up a rectangular dimpled channel for gas turbine hot components and designed different configurations of rib promoters in the corner regions to heat transfer enhancement. Chang et al [ 17 ] reported on heat transfer and pressure drop features of radially rotating ribbed channels with and without dimples.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [ 15 ] experimentally and numerically studied the heat transfer and pressure drop characteristics in blade trailing edge trapezoidal and rectangular cooling passages with dimples under the effect of ejection slots. Lauffer et al [ 16 ] set up a rectangular dimpled channel for gas turbine hot components and designed different configurations of rib promoters in the corner regions to heat transfer enhancement. Chang et al [ 17 ] reported on heat transfer and pressure drop features of radially rotating ribbed channels with and without dimples.…”
Section: Introductionmentioning
confidence: 99%